Benefits of Assessing Risk in Maritime Navigation Using IALA and LINZ Methods - Seepersad, Dawn; Eriksson, Omar Frits; Greenland, Adam; Miller, Keith (The International Hydrographic Review, 2020)
Introduction of the Automatic Identification System (AIS) for shipping has led to use of archived data in risk assessment for maritime navigation. The IWRAP software from the International Association of Aids to Navigation and Lighthouse Authorities (IALA) makes use of statistics derived from AIS data to determine likelihood of collision and grounding events in waterways where maritime traffic follows regular routes. Alternatively, the New Zealand Hydrographic Authority implemented a weighted overlay in a Geographic Information System (GIS) using AIS data together with further geographical information of a waterway to determine risk. These methods are tested in Trinidadian waters of the Gulf of Paria to identify benefits. It is concluded that each method offers a different contribution to the decision making process for improvement to the safety of navigation.